Implementation of Takagi Sugeno method as fuzzy logic control with multiple sensors on fire fighter robot prototype navigation - Mohamad Pauzi, Alif Aiman (2022)
Autonomous mobile robot will become an interest by many researchers. Due to needs of an effective navigational system for the robot, many approach was purposed to control the reliability of the system in order to achieve an optimum control system respond. Nowadays, AI was used as one of the approached to enhance the decision making by the robot itself without depending on the user. In this development, multiple sensors were implemented to increase the detection accuracy of the prototype during navigate on constantly changing environment. By using multiple sensors (ultrasonic sensor) it means that, it will have more input information so, in order to manage all of this data information, intelligent control strategy was required to achieve an optimum output in term of efficiency and accuracy. On this development, previous prototype was upgraded into more intelligent system. Fuzzy Logic was introduced to this development by using a Takagi Sugeno inference method. In this project Fuzzy control was designed with aid of computing software (MATLAB) and by using a Arduino MEGA controller Fuzzy logic control was apply to realize the real-time simulation for the robot navigation. The fire detection unit by using IR sensor module was purposed to make sure it can scan the IR wave generated by the flame. Differential steering method was selected for semi-autonomous robot driving system and it was powered by 2 DC motor for the robot navigation. All the function of the robot is tested in order to evaluate the capability of the system on the robot by referred to the project scope. On this development, the effectiveness of the system was vary with the number of Fuzzy Rule. The effectiveness of the Fuzzy control was observed by the time taken for the prototype completed the route and the time respond for the prototype to avoid obstacle during the navigation inside the test rig.